Expanding the applicability of ASTM D3233A Pin & Vee Block method to evaluate lubricant emulsions for cutting applications. (2nd January 2023) - Georgiou, E.P.; Drees, D.; Helmetag, K.; Van der Donck, T.; Lopes, L.M.; Semal, F.; De Bilde, M.; Anderson, M.
ABSTRACT: ASTM Method D3233A uses a Pin&Vee Block tester to evaluate cutting fluids. However, the standard defines a steel-steel contact, uses a small volume of lubricant, and the test report is limited to the 'ultimate failure load'. With our approach, we bring testing closer to reality, using different metallurgies and testing the oils in aqueous emulsion-form. We monitor the frictional torque throughout increasing load, so that differences between products are revealed that are not visible in failure load alone. By modifying lubrication to recirculated or misted conditions, we simulate cutting of forming operations. Consequently, this provides an additional tool for cost efficient ranking of cutting fluids, based on an industry-accepted instrument. We demonstrate same ranking of cutting fluids as well established Tapping Torque Tests, with the advantage of using a simplified and lower cost configuration. Developing a standardized test protocol involves more work on reproducibility and correlation to real machining processes. GRAPHICAL ABSTRACT: UF0001